2.1.26 \(x u_x+y u_y=u\) (Example 3.5.1 in Lokenath Debnath)

problem number 26

Added June 2, 2019.

From example 3.5.1, page 210 nonlinear pde’s by Lokenath Debnath, 3rd edition.

Solve for \(u(x,y)\) \begin {align*} x u_x+y u_y&=u \end {align*}

Mathematica


\[\left \{\left \{u(x,y)\to x c_1\left (\frac {y}{x}\right )\right \}\right \}\]

Maple


\[u \left (x , y\right ) = x \mathit {\_F1} \left (\frac {y}{x}\right )\]

Hand solution

Solve \[ xu_{x}+yu_{y}=u \] Using the Lagrange-charpit method\[ \frac {dx}{x}=\frac {dy}{y}=\frac {du}{u}\] The first pair of equations gives \[ x=C_{1}y \] And \(\frac {dx}{x}=\frac {du}{u}\) gives\[ x=C_{2}u \] Since \(C_{2}=G\left ( C_{1}\right ) \) then \(\frac {x}{u}=G\left ( \frac {x}{y}\right ) \) or \(u=xG^{-1}\left ( \frac {x}{y}\right ) \). Let \(G^{-1}=F\). Then the solution \[ u\left ( x,y\right ) =xF\left ( \frac {x}{y}\right ) \]

________________________________________________________________________________________